Formation ofscientific of attitudes of N. I. Nijniy (1916–2003)of the scientific way to agro-economics - Chalavan, V. A. (History of science and technology, 2014)
Factors of formation of Professor Nikolai Ivanovich Nijniyas an outstan dingscientist in the fieldof payment for labor from the post-warperiodof Soviet era were explored in the article.It was foundthat the characteristicsofscientific activity passage of scientist are determined byinternal and external factors, in particular, it was found that the issueof scientist’s researchof payment for laborissueshas been formedduring historical eventswhich led to compulsory purchase of rural workersfrom production andefficiency.